Satellite tracking of Wandering albatrosses - Jouventin, Pierre; Weimerskirch, Henri (Nature (London), 1990)
ALTHOUGH the study of seabirds in their land-based breeding colonies has attracted much attention, an understanding of their ecology at sea, particularly their foraging range and the location of their feeding zones, remains a major challenge 1 . The foraging range of pelagic feeders nesting on a given colony or island is purely speculative 2,3 . Since the eighteenth century 4 , the Wandering albatross ( Diomedea exulans ) has been thought to be one of the most widely ranging seabirds, and breeders are thought to travel up to 1,800 km from the nest on foraging trips 5,6 . Here, we describe the first successful tracking of a bird using satellite telemetry. Tracks of Wandering albatrosses in the southwestern Indian Ocean showed that they covered between 3,600 and 15,000 km in a single foraging trip during an incubation shift. They flew at speeds of up to 80 km per h and over distances of up to 900 km per day. They remained active at night, particularly on moonlit nights and wind appeared to have a major influence on the foraging strategy of these albatrosses. Detailed knowledge of their movements at sea may prove critical to the conservation of the Wandering albatross and particularly of the closely related Amsterdam albatross ( D. amsterdamensis ), both of which are endangered 7–9 .